Application Of Sugeno's Fuzzy Inference System In Determining Inventory Goat Milk - Windah Sahara (Yayasan Kita Menulis, 2022)
Goat milk is one of the milk that is traded by the community because this milk has many benefits that are good for the health of the body and prevent bone damage in old age. Thalebkawnhinca Farm is a business that trades goat's milk both per liter and per pack. The erratic supply of goat's milk causes consumer demand cannot be fulfilled and the milk sales process becomes hampered. Therefore, this study aims to apply fuzzy logic with the Sugeno method in determining the amount of goat milk supply at Thalebkawanhinca Farm based on data on demand and sales of milk in April 2021. Based on data on demand and sales of goat's milk, the amount of milk supply that must be added if known demand of 90 liters and sales of 75 liters amounted to 25.1953125 liters. The result of this research is the implementation of a milk supply system that can be used in determining and providing information on the amount of goat's milk supply to the owner of the Thalebkawanhinca Farm.